Climate controls on ecosystem-atmosphere carbon exchange and hydrological dynamics in Rocky Mountain fens - Millar, David, author; Cooper, David, advisor; Dwire, Kate, committee member; Hubbard, Robert, committee member; Ronayne, Michael, committee member; von Fischer, Joseph, committee member (Colorado State University. Libraries, 2015)
Groundwater fed peatlands known as fens are among the most important ecosystems in the Rocky Mountains of North America. These wetlands have sequestered atmospheric carbon dioxide for several millennia, provide important habitat for wildlife, and serve as refugia for regionally-rare plant species typically found in boreal regions. Perennially high water tables are critical for ecosystem functioning in fens, and provide conditions that support the development and persistence of organic soils. It is unclear how Rocky Mountain fens will respond to a changing climate, and those found at lower elevations may be particularly susceptible, where changes in hydrological cycles that control water tables are likely to be greatest. Further, it is unclear how regionally variable monsoon rainfall influences water tables and carbon dynamics, late in the growing season. In this dissertation I addressed the following questions: 1) How does ecosystem-atmosphere CO₂ exchange vary with elevation and monsoon influence in Rocky Mountain fens? 2) How do snowmelt dynamics at high and low elevations and varying monsoon influence affect groundwater dynamics in fens of the Rocky Mountains? 3) How will mountain fen hydrological dynamics potentially change under a future climate, and what will be the subsequent impact on ecosystem-atmosphere C exchange? My results show that net ecosystem production was higher for fens located at high elevations compared to those found at lower elevations. This was reflected in the negative correlation of growing season net ecosystem production with air temperature, and positive correlation with water table position, as the high elevation sites had the lowest air temperatures and highest water tables. Study fens in the San Juan Mountains of southwest Colorado received almost twice as much late summer precipitation than those in the Medicine Bow Mountains of Wyoming, causing more frequent water table rises. However, differences in net ecosystem production associated directly with varying monsoon influence were less discernable. Peak snow water equivalent was lower for fens located at low elevations, and the snow-free season occurred approximately one month earlier at these sites compared to high elevation fens. The earlier onset of snow-free conditions led to steady declines in water table position early in the growing season at the low elevation fens, driven primarily by evapotranspiration. Under two future climate modeling scenarios at a low elevation fen, warmer air temperatures increased the proportions of winter precipitation that fell as rain, and peak snow water equivalent was reduced along with the number of days which snowpack persisted. Results from a coupled carbon exchange and hydrological model showed these changes in hydrological processes led to lower water tables that persisted through the growing season, and subsequently impacted ecosystem-atmosphere C exchange. Under the future climate scenarios, the overall global warming potential of gaseous C emissions increased as a result of increased ecosystem respiration, despite decreases in methane emissions. Further, the future climate scenarios suggest that the sustainability of low-elevation fens may be in jeopardy, as losses of C exceed inputs.